Changes and relationship of climate and late-rice yield in chenzhou city of south hunan province of CHINA (Bangladesh Journal of Botany, 2023)
The changes and relationship of climate parameters and late-rice yield per unit area during the growth periods of late-rice from 2010 to 2019 were quantitatively analyzed in order to provide scientific guidance for countermeasures against climate change and sustainable production of late-rice. The climate parameters include cumulative daily sunshine hours (S), mean daily temperature (T), cumulative daily precipitation (P), mean daily relative humidity (H), daily highest and lowest temperatures (Th and Tl), days of high temperatures (DT ≥ 30℃ and DTh ≥ 35℃) and low temperature (DTl < 15℃). Results showed that: (i) Late-rice yield was significantly increased quadratically from 5621.33 kg hm2 in 2010 to 6333.65 kg hm2 in 2019 with a mean of 5959.2 kg hm2.  (ii ) According to the suitable climate conditions for growth of late-rice, T and P were low but H was suitable in the whole field growth period of late-rice, T was suitable in the transplanting-tillering stage, but was low in the booting-heading and milk ripening-mature stage. DT ≥ 30℃, DTh  ≥ 35℃ and   DTl < 15℃ was meanly 7.7, 7.5 and 6.4 d, respectively, which showed possible occurrence of the damages to late-rice due to high and low temperatures. iii) Only T, Th and Tl in the booting-heading stage showed significant positive correlation with year, and the optimal regression models were in quadratic and exponential types. The climate parameters of S, T and Th in the boot-heading stage were significantly positively correlated with late-rice yield, and the optimal regression models were all in quadratic types. Daily highest temperature (Th) affected late-rice yield most (61.04%), followed by T (36.50%), and S affected least (2.46%). Considering the current conflict in the field planting periods between tobacco and late-rice, late rice varieties needs to be bred with short growth period and high tolerance to both high and low temperatures.Bangladesh J. Bot. 52(2): 639-647, 2023 (June) Special